Epidemiological Pattern of Births from the Largest Surveillance Database of Live Births in Brazil "SINASC" before and during the COVID-19 Pandemic in the Brazilian Amazon - Daniele Melo Sardinha; Andréa Maria Da Silva Luz; Kátia Raquel Almeida Carneiro; Mauro Daniel Rodrigues Paixão; Sebastião Kauã De Sousa Bispo; Natasha Cristina Oliveira Andrade; Juliane Lima Alencar; Tamires De Nazaré Soares; Joyce Dos Santos Freitas; Rubenilson Caldas Valois; Ana Lúcia da Silva Ferreira; Karla Valéria Batista Lima; et al. (Archives of Current Research International, 2022)
The surveillance of live births in Brazil has been carried out since 1990 by the Information System on Live Births (SINASC), which was implemented by the Ministry of Health aiming at standardized registration on a national level. The state of Pará is part of the Brazilian Amazon, northern Brazil, which has several unique characteristics. Thus, the purpose of this study was to identify the epidemiological pattern of live births before and during the pandemic of COVID-19 in the state of Pará, 2016 to 2020. This is an ecological epidemiological time-series study, using epidemiological surveillance data from DATASUS, referring to the Live Births Information System (SINASC). These are data that have been treated by surveillance and are in aggregate format. The study population is the live births residing in the state of Pará, in the period from 2016 to 2020. The data collection instrument was the Declaration of Live Births (DLB). There were 689,454 live births, and the highest rates of births were and continued to remain in the Marajó II, Baixo Amazonas, Xingu, and Tapajós regions. The Metropolitan I and Araguaia regions were and continue to be the lowest rates in the state. Age of the mother 15 to 19 years old 22.29%, 20 to 24 years old 30.05% and 25 to 29 years old 22.58%, most of the single pregnancy type 98.32%, prenatal consultations, performed 7 or more 48.10%, followed by 4 to 6 consultations 33.98%, most presented 7 or more years of the study 48.10%, followed by 3 to 6 years 33.98%. Represented 51.21% male and 48.77% female. The occurrence of congenital anomalies represented 0.52% of live births. Another congenital malformation and deformity were the most prevalent at 25.53%, followed by Congenital deformities of the feet 14.90%, Other congenital malformations of the nervous system 14.84%, and Other congenital malformations 10.77%, Cleft lip, and cleft palate 8.88%, Other congenital malformations digestive tract 8.10%. The demographic transition has already occurred for several decades, including the reduction of fertility and birth rate, so our study showed that the reduction in the number of live births was already a reality in the country, but we emphasize that this reduction was enhanced by the pandemic. We observed greater adherence to prenatal care and a lower prevalence of low birth weight compared to other studies, but the limitation was the absence of studies in the same place of the research. Regarding data incompleteness, we emphasize the ignored fields that reflect the fragility in the surveillance of live births, which was reinforced by the literature.